Cardiovascular disease risk among breast cancer survivors: an evolutionary concept analysis - Vo JB; Nolan TS; Vance DE; Patrician PA; Meneses K (Dove Medical Press, 2017)
Jacqueline B Vo,1 Timiya S Nolan,1 David E Vance,1 Patricia A Patrician,2 Karen Meneses1 1Office of Research and Scholarship, 2Department of Family, Community Health, and Systems, University of Alabama at Birmingham School of Nursing, Birmingham, AL, USA Background: More than 3.5 million breast cancer survivors are living in the US, and the overall five-year survival rate is approaching 90%. With increased survival and cancer treatment-related cardiotoxicities, there has been a rise in cardiovascular diseases among breast cancer survivors. Yet, cardiovascular disease risk among breast cancer survivors has not been well conceptualized. The purpose of this article was to analyze and define the concept of cardiovascular disease risk among breast cancer survivors. Methods: The databases CINAHL, EMBASE, and PubMed were used to identify articles that explored cardiovascular disease risk among breast cancer survivors. The search yielded 357 articles, which were reviewed for eligibility. Thirty articles were selected based on the inclusion/exclusion criteria. The concept of cardiovascular disease risk among breast cancer survivors was analyzed using Rodgers’ evolutionary concept analysis method. Results: The analysis suggests that cardiovascular disease risk among breast cancer survivors consists of several attributes: cancer treatment (chemotherapy, targeted therapies, radiation therapy, and endocrine therapy), modifiable risk factors (obesity, physical inactivity, poor diet, and smoking), and nonmodifiable risk factors (age, family history, and race). The antecedent identified includes breast cancer diagnosis and the consequence identified includes the development of cardiovascular disease. Conclusion: Findings suggest the need for increased education and understanding of cardiovascular disease risk among health care providers and patients. Survivorship care plans can incorporate cardiovascular disease risk monitoring and screening. Future research is needed to explore interventions and develop stratified screening guidelines for breast cancer survivors. Keywords: breast cancer survivors, cardiovascular disease risk, Rodgers’ evolutionary concept analysis method, cancer survivorship, cardiotoxicity